Hydrophobic bio-based ultraviolet curing resin, and preparation method and coating thereof

By introducing tung oleic anhydride into the coating, the hydrophobic bio-based ultraviolet curing resin is formed, which solves the problem of insufficient comprehensive performance of existing coatings, achieves better flexibility, adhesion and hydrophobic properties, and meets the needs of outdoor waterproof applications. .

CN119463058APending Publication Date: 2025-02-18PUYANG ZHANCHEN NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411600590.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The comprehensive performance of existing coatings is not high enough to meet current usage needs.

Method used

The hydrophobic bio-based ultraviolet curing resin is used, which consists of epoxy resin, acrylic acid, acid anhydride, UV monomer, polymerization inhibitor and catalyst. By introducing tung oleic anhydride, the flexibility, adhesion and hydrophobic properties of the resin are improved.

Benefits of technology

It improves the flexibility, adhesion and hydrophobic properties of the resin, reduces the volume shrinkage rate during the curing process, enhances the mechanical properties and thermal stability of the material, and meets the needs of photocured coatings in outdoor waterproof applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463058A_ABST
    Figure CN119463058A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides hydrophobic bio-based ultraviolet curing resin, a preparation method thereof and a coating. The hydrophobic bio-based ultraviolet curing resin comprises the following raw materials in parts by weight: 380-450 parts of epoxy resin; 70 to 100 parts of acrylic acid; 260 to 700 parts of acid anhydride; 300 to 400 parts of a UV monomer; 2-4 parts of a polymerization inhibitor; 4-10 parts of a catalyst; wherein the anhydride comprises tung oil anhydride. According to the hydrophobic bio-based ultraviolet curing resin, the preparation method thereof and the coating provided by the embodiment of the invention, tung oil anhydride is introduced, so that the product has the performance of a tung oil molecular structure, the hydrophobic performance and the flexibility of the resin are improved due to a long-chain alkyl structure, and meanwhile, the distribution of carbon-carbon double bonds is diluted; the volume shrinkage rate in the resin curing process is reduced, so that the adhesive force of the resin is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of coatings, and in particular relates to a hydrophobic bio-based ultraviolet light-curing resin and a preparation method and coating thereof. Background Art

[0002] Ultraviolet Curing Resin, also known as UV resin, is a special oligomer that can undergo physical and chemical changes rapidly under ultraviolet (UV) irradiation to achieve curing. This process is called photocuring or UV curing. UV resins usually contain reactive groups such as unsaturated double bonds or epoxy groups, which can quickly cross-link to form solid substances under the action of photoinitiators.

[0003] As people pay more and more attention to environmental protection and energy utilization, the emission of volatile organic compounds in traditional solvent-based coatings is increasingly restricted, and environmentally friendly coatings have become one of the main directions of the development of the coatings industry. UV-curable coatings are an environmentally friendly and energy-saving coating developed in the 1960s. With its advantages of fast curing speed, high production efficiency, excellent material properties, and less environmental pollution, it has become one of the varieties with an increasing share in wood furniture coatings.

[0004] UV curing resin is the main part of UV curing coating, which determines the basic performance of cured coating. Epoxy acrylate is the most widely used UV curing resin. The main characteristics of epoxy acrylate include: fast photocuring reaction rate, high hardness and tensile strength after curing, high film gloss, and excellent chemical corrosion resistance. Its disadvantage is that the cured film is not flexible enough and brittle.

[0005] In summary, the comprehensive performance of current coatings is not high enough to meet current usage needs. Summary of the invention

[0006] In view of this, the embodiments of the present application provide a hydrophobic bio-based UV-curable resin and a preparation method and coating thereof to solve the technical problem that the comprehensive performance of existing coatings is not high enough to meet current usage requirements.

[0007] In a first aspect, an embodiment of the present application provides a hydrophobic bio-based UV-curable resin, comprising the following raw materials in parts by weight:

[0008] 380-450 parts of epoxy resin;

[0009] Acrylic acid 70-100 parts;

[0010] 260-700 parts of acid anhydride;

[0011] 300-400 parts of UV monomer;

[0012] 2 to 4 parts of inhibitor;

[0013] 4 to 10 parts of catalyst;

[0014] Wherein, the acid anhydride includes tung oil anhydride.

[0015] In some embodiments, the anhydride further comprises phthalic anhydride;

[0016] Wherein, the weight ratio of the tung oil anhydride to the phthalic anhydride is (20-45): (2-12).

[0017] In some embodiments, the acid anhydride further comprises tetrahydrophthalic anhydride and hexahydrophthalic anhydride, and the weight ratio of the phthalic anhydride, the tetrahydrophthalic anhydride and the hexahydrophthalic anhydride is (1-6):(1-6):(1-6).

[0018] In some embodiments, the UV monomer includes any two of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and 1,6-hexanediol diacrylate.

[0019] In some embodiments, the epoxy resin is 128 epoxy resin. Alternatively, in other embodiments, the epoxy resin may be replaced with epichlorohydrin or other epoxy diluents.

[0020] In some embodiments, the inhibitor is any one of p-hydroxyanisole and hydroquinone.

[0021] In some embodiments, the catalyst is any one of triphenylphosphine, triethylamine, dimethylbenzylamine, triethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, and tetraethylammonium bromide.

[0022] In a second aspect, the present application provides a method for preparing a hydrophobic bio-based UV-curable resin, comprising:

[0023] According to the hydrophobic bio-based UV-curable resin of the first aspect, raw materials are provided for preparation: epoxy resin, acrylic acid, acid anhydride, UV monomer, inhibitor and catalyst; wherein the UV monomer comprises a first monomer and a second monomer;

[0024] mixing the acid anhydride with the first monomer to react to obtain a mixed half-ester acid;

[0025] The epoxy resin, the acrylic acid, the second monomer, the polymerization inhibitor and the catalyst are mixed with the mixed half-ester acid to perform an esterification reaction to obtain the hydrophobic bio-based ultraviolet curing resin.

[0026] In some embodiments, the first monomer is any one of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxyethyl methacrylate;

[0027] The second monomer is 1,6-hexanediol diacrylate.

[0028] In some embodiments, the mixing of the acid anhydride and the first monomer to obtain a mixed half-ester acid comprises:

[0029] heating the reaction system;

[0030] When the temperature of the reaction system rises to 90°C to 110°C, keep it warm for 1.5h to 2.5h;

[0031] The acid value is detected. When the acid value is within the range of 110 KOH / g to 130 mg KOH / g, the temperature is lowered to 50° C. to 70° C. to obtain the mixed half-ester acid.

[0032] In some embodiments, the esterification reaction conditions include:

[0033] Control the reaction temperature at 85°C to 95°C and keep it for 0.5h to 1.5h;

[0034] Control the reaction temperature at 100°C to 105°C for 0.5h to 1.5h;

[0035] Control the reaction temperature at 115°C to 117°C and keep it for 1.5h to 2.5h;

[0036] The acid value is detected once every hour until the acid value drops to 3 mgKOH / g to 8 mgKOH / g, then the temperature is lowered and vacuum is drawn at 60° C. to 90° C. to obtain the hydrophobic bio-based UV-curable resin.

[0037] In a third aspect, an embodiment of the present application provides a coating, comprising the hydrophobic bio-based UV-curable resin described in the first aspect or the hydrophobic bio-based UV-curable resin prepared by the preparation method described in the second aspect.

[0038] The hydrophobic bio-based UV-curable resin provided in the embodiment of the present application, by introducing tung oil anhydride, the product has the performance of the tung oil molecular structure, the long-chain hydrocarbon structure brings the improvement of hydrophobicity and the flexibility of the resin itself, and dilutes the distribution of carbon-carbon double bonds at the same time, reduces the volume shrinkage during the resin curing process, thereby improving the adhesion of the resin. Specifically, tung oil anhydride can be added to the system as a reactive diluent, which helps to reduce the viscosity of the resin and improve the processing performance. At the same time, it can also participate in subsequent chemical reactions and become a part of the cured resin, and will not affect the performance of the final product like a non-reactive diluent. Since tung oil anhydride is derived from natural plant oil (tung oil), it has certain bio-based characteristics, and its introduction can improve the biodegradability and environmental friendliness of the resin. In addition, the long-chain fatty acid structure in tung oil anhydride can give the resin better flexibility, chemical resistance and hydrophobicity. By adjusting the ratio of tung oil anhydride to epoxy resin, the cross-linking density of the cured product can be effectively adjusted, thereby affecting the mechanical properties and thermal stability of the material such as hardness and toughness. Tung oil anhydride contains unsaturated double bonds, which can quickly undergo free radical polymerization or addition reaction under ultraviolet light, accelerating the curing process of the entire resin system and improving production efficiency.

[0039] The embodiment of the present application provides a method for preparing a hydrophobic bio-based UV-curable resin, wherein tung oil anhydride in the acid anhydride is used to undergo a ring-opening reaction with the hydroxyl group in the hydroxyethyl acrylate molecule in the UV monomer, thereby introducing the main molecular structure of tung oil into the resin molecular structure, and then after the resin is formed into a film, it has performance characteristics such as hydrophobicity and flexibility similar to tung oil. However, since the molecular weight of tung oil anhydride itself is relatively large, when used in combination with other organic anhydrides, the viscosity of the resin product can be effectively reduced, which is beneficial to the coating construction using this resin.

[0040] The coating provided in the embodiment of the present application, due to the introduction of tung oil anhydride, the obtained UV-curable resin contains a certain amount of bio-based degradable components, the resin also has a good curing speed, and at the same time has better flexibility, adhesion and hydrophobicity than epoxy acrylate, and can meet the application requirements of light-curing coatings in outdoor waterproofing. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 It is a schematic flow chart of a method for preparing a hydrophobic bio-based UV-curable resin provided in an embodiment of the present application. DETAILED DESCRIPTION

[0043] In the following description, specific details such as specific system structures, technologies, etc. are proposed for the purpose of illustration rather than limitation, so as to provide a thorough understanding of the embodiments of the present application. However, it should be clear to those skilled in the art that the embodiments of the present application can also be implemented in other embodiments without these specific details. In other cases, detailed descriptions of well-known systems, devices, circuits, and methods are omitted to prevent unnecessary details from hindering the description of the embodiments of the present application.

[0044] It should also be understood that the term “and / or” used in the description of the embodiments of the present application and the appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0045] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0046] It should be understood that the orientation or position relationship indicated by terms such as "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" are based on the orientation or position relationship shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0047] In addition, in the description of the embodiments of the present application and the appended claims, the terms "first", "second", "third", etc. are only used to distinguish the descriptions and cannot be understood as indicating or implying relative importance.

[0048] References to "some embodiments" or "some embodiments" etc. described in the specification of the embodiments of the present application mean that one or more embodiments of the embodiments of the present application include specific features, structures or characteristics described in conjunction with the embodiment. Thus, the statements "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear in the different parts of this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways. "Multiple" refers to two or more.

[0049] UV-curable resin is the main part of UV-curable coatings, which determines the basic properties of cured coatings. Epoxy acrylate is the most widely used UV-curable resin. The main characteristics of epoxy acrylate include: fast photocuring reaction rate, high hardness and tensile strength after curing, high film gloss, and excellent chemical corrosion resistance. Its disadvantage is that the cured film is not flexible enough and brittle. The use of renewable vegetable oil resources to synthesize excellent bio-based UV resins is of great significance for the high-value utilization of vegetable oil resources and the sustainable development of the UV resin industry.

[0050] In view of this, the first aspect of the embodiment of the present application provides a hydrophobic bio-based UV-curable resin, comprising the following raw materials in parts by weight:

[0051] 380-450 parts of epoxy resin;

[0052] Acrylic acid 70-100 parts;

[0053] 260-700 parts of acid anhydride;

[0054] 300-400 parts of UV monomer;

[0055] 2 to 4 parts of inhibitor;

[0056] 4 to 10 parts of catalyst;

[0057] Wherein, the acid anhydride includes tung oil anhydride.

[0058] The hydrophobic bio-based UV-curable resin provided in the embodiment of the present application, epoxy resin is one of the main components of the system, providing basic mechanical properties and bonding properties. It can react with anhydride to form a thermosetting network structure, enhancing the chemical resistance and mechanical strength of the final product; acrylic acid or its derivatives can improve the flexibility, adhesion and weather resistance of the resin. In addition, they can also improve the gloss and smoothness of the coating; anhydride is used as a cross-linking agent, and reacts with epoxy resin to form a polymer compound with a three-dimensional network structure, thereby giving the material better heat resistance, chemical resistance and mechanical strength. Tung oil anhydride is derived from natural plant oil and belongs to a bio-based material, which helps to improve the environmental performance of the material; UV monomers generally refer to small molecule compounds containing polymerizable functional groups, such as acrylate monomers. These monomers can be rapidly polymerized under ultraviolet light, accelerate the curing process, and can adjust the hardness, flexibility and surface properties of the final product; the role of the inhibitor is to prevent the free radical polymerization of double bonds of the resin during the synthesis process. Selecting the right inhibitor is crucial to ensure efficient and uniform curing; the role of the catalyst is to promote the chemical reaction between the epoxy resin and the anhydride, reduce the activation energy of the reaction, speed up the curing speed, and also affect the physical and chemical properties of the cured product. In some cases, the catalyst can also regulate the side reactions produced during the curing process and improve the stability and quality of the product.

[0059] In the application, the tung oil anhydride in the acid anhydride is used to undergo a ring-opening reaction with the hydroxyl group in the hydroxyethyl acrylate molecule in the UV monomer, thereby introducing the main molecular structure of tung oil into the resin molecular structure, and then after the resin film is formed, it has performance characteristics such as hydrophobicity and flexibility similar to tung oil. However, since the molecular weight of tung oil anhydride itself is relatively large, it can effectively reduce the viscosity of the resin product when used in combination with other organic acid anhydrides. By introducing tung oil anhydride, the product has the properties of the tung oil molecular structure. The long-chain hydrocarbon structure brings about the improvement of hydrophobicity and the flexibility of the resin itself, while diluting the distribution of carbon-carbon double bonds, reducing the volume shrinkage rate during the resin curing process, and improving the adhesion of the resin.

[0060] In some embodiments, the epoxy resin is 128 epoxy resin. Optionally, in other embodiments, the epoxy resin can be replaced with epichlorohydrin or other epoxy diluents. This is because 128 epoxy resin is a bisphenol A type epoxy resin with good mechanical strength, chemical resistance and electrical insulation. Due to its high molecular weight and good processing properties, 128 epoxy resin is an ideal choice for making high-performance UV-curable resins. Epichlorohydrin itself is not a resin, but an important organic chemical raw material for synthesizing epoxy resins. However, under certain conditions, it can be added to the epoxy resin system as a diluent to reduce viscosity, improve process performance or reduce costs. When used as a diluent, epichlorohydrin can participate in the subsequent curing reaction and become part of the final cured product. In addition to epichlorohydrin, there are many other types of epoxy diluents that can be used to adjust the properties of the resin system, such as monofunctional epoxy diluents (such as phenyl glycidyl ether), difunctional epoxy diluents (such as butyl glycidyl ether), etc. These diluents can significantly reduce the viscosity of the resin, improve fluidity, and facilitate construction; at the same time, they can also participate in the curing reaction and affect the physical and chemical properties of the final product.

[0061] In some embodiments, the anhydride also includes phthalic anhydride; wherein the weight ratio of tung oil anhydride to phthalic anhydride is (20-45): (2-12). Specifically, the weight ratio of tung oil anhydride to phthalic anhydride can be any value within the range of (20-45): (2-12), such as 10:1, 5:3, 45:2, 45:12, 44:15, 43:4, 11:2, etc. In this way, using one of tung oil anhydride and phthalic anhydride within the above ratio range can effectively balance rigidity and toughness. Tung oil anhydride is derived from natural plant oil and has a longer carbon chain structure, which can give the material better flexibility and impact resistance. Phthalic anhydride is a short-chain anhydride that can provide a higher cross-linking density, making the material harder and more resistant to chemicals. By adjusting the ratio of the two, it is possible to ensure that the material has a certain hardness while maintaining good flexibility to meet the needs of different application scenarios. Secondly, it can improve hydrophobicity. Tung oil anhydride contains a long fatty chain, which helps to improve the hydrophobicity of the material, reduce water absorption and extend the service life. The introduction of phthalic anhydride can increase the number of cross-linking points, improve the overall density of the material, and further enhance the hydrophobic effect. Thirdly, it can optimize the curing characteristics. The reactivity of different anhydrides varies. The mixed use of tung oil anhydride and phthalic anhydride can regulate the curing speed and avoid the problem of too fast or too slow curing caused by a single anhydride. The appropriate ratio helps to achieve uniform and sufficient curing and reduce defects such as bubbles and cracks that may occur during the curing process. Finally, the bio-based content can be increased. As a bio-based material, the higher proportion of tung oil anhydride in the formula helps to improve the sustainability and environmental friendliness of the entire system. At the same time, the right amount of phthalic anhydride can ensure that the material has sufficient heat resistance and mechanical strength, and will not sacrifice performance due to excessive use of bio-based ingredients.

[0062] In some embodiments, the anhydride also includes tetrahydrophthalic anhydride and hexahydrophthalic anhydride, and the weight ratio of phthalic anhydride, tetrahydrophthalic anhydride and hexahydrophthalic anhydride is (1-6): (1-6): (1-6). Specifically, the weight ratio of phthalic anhydride, tetrahydrophthalic anhydride and hexahydrophthalic anhydride can be any value within the range of (1-6): (1-6): (1-6) such as 1:1:1, 1:6:6, 6:1:1, 6:6:1, etc. In this way, the cross-linking density can be optimized. Phthalic anhydride has a shorter carbon chain and can provide a high cross-linking density, making the material harder and more resistant to chemicals. Tetrahydrophthalic anhydride is between phthalic anhydride and hexahydrophthalic anhydride, providing a medium-length carbon chain, which helps to balance rigidity and toughness. Hexahydrophthalic anhydride has a longer carbon chain, which can increase the flexibility and impact resistance of the material.

[0063] In some embodiments, the UV monomer includes any two of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and 1,6-hexanediol diacrylate. In a preferred embodiment, the UV monomer includes hydroxyethyl acrylate and 1,6-hexanediol diacrylate. In this way, hydroxyethyl acrylate alone can improve adhesion. The hydroxyethyl acrylate molecule contains hydroxyl groups (-OH), which can form hydrogen bonds or chemical bonds with the surface of the substrate, thereby improving the adhesion of the coating. Improve flexibility. The long chain structure of hydroxyethyl acrylate enables it to provide a certain flexibility, which helps to reduce cracks in the coating under bending or impact. The presence of hydroxyl groups can increase the hydrophilicity of the material, but this may not be the main purpose in this formulation because the overall goal is to improve hydrophobicity. However, an appropriate amount of hydrophilicity helps to improve the wettability and leveling of the coating. Hydroxyethyl acrylate has good chemical stability and can improve the weather resistance and aging resistance of the coating. 1,6-Hexanediol diacrylate alone can increase the crosslinking density. The 1,6-Hexanediol diacrylate molecule contains two acrylate groups, which can form a highly crosslinked network structure and improve the hardness, wear resistance and chemical resistance of the material. The long chain structure and high crosslinking density of 1,6-Hexanediol diacrylate enable it to provide higher rigidity and heat resistance, and is suitable for applications that require high temperature resistance. 1,6-Hexanediol diacrylate has a lower viscosity, which can improve the fluidity and processing properties of the resin, and facilitate construction and coating. The synergistic effect of the combination of the two can achieve comprehensive optimization of the coating in terms of flexibility, hardness, adhesion and chemical resistance. The combination of the two can regulate the curing speed and achieve uniform and sufficient curing. The hydroxyl group of hydroxyethyl acrylate can better interact with the free radicals generated by the inhibitor to promote the curing reaction. The bifunctional group of 1,6-Hexanediol diacrylate can provide more crosslinking points to ensure that the cured material has a high crosslinking density. The chemical stability of hydroxyethyl acrylate and the highly cross-linked structure of 1,6-hexanediol diacrylate work together to improve the weather resistance and durability of the coating, allowing it to maintain stable performance for a long time in outdoor environments. The hydroxyl group of hydroxyethyl acrylate can improve the wettability and leveling of the coating, making the surface smoother and flatter. The low viscosity of 1,6-hexanediol diacrylate helps to improve the fluidity and uniformity of the coating.

[0064] In certain embodiments, the inhibitor is any one of p-hydroxyanisole and hydroquinone. P-hydroxyanisole is a very effective free radical scavenger, which can react with free radicals to form stable compounds quickly, thereby preventing the continuation of polymerization. It has good thermal stability and chemical stability, and can play a role in a wide temperature range. It has good solubility in many organic solvents and is easy to mix with other ingredients. Hydroquinone is a powerful antioxidant that can effectively capture free radicals and interrupt chain oxidation reactions.

[0065] In some embodiments, the catalyst is any one of triphenylphosphine, triethylamine, dimethylbenzylamine, triethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, and tetraethylammonium bromide. Among them, triphenylphosphine can effectively promote the cross-linking reaction between epoxy resin and acid anhydride and improve the curing rate. Triphenylphosphine has low volatility and is suitable for curing processes that require long-term stability. Triphenylphosphine has good heat resistance and is suitable for high-temperature curing conditions. Triethylamine is a strong alkaline catalyst that can significantly accelerate the reaction rate of epoxy resin and acid anhydride. Triethylamine can achieve rapid curing and is suitable for applications that require rapid prototyping. Triethylamine has high volatility and may affect the operating environment and the stability of the finished product. Dimethylbenzylamine is an efficient catalyst that can significantly increase the cross-linking rate of epoxy resin and acid anhydride. Dimethylbenzylamine has good solubility in a variety of resins and monomers and is easy to disperse and mix. Dimethylbenzylamine has a low tendency to yellowing during the curing process and is suitable for applications that require high color.

[0066] The present application also provides a method for preparing a hydrophobic bio-based UV-curable resin. Figure 1 As shown, including:

[0067] S10, providing raw materials for preparing the hydrophobic bio-based UV-curable resin according to the first aspect: epoxy resin, acrylic acid, acid anhydride, UV monomer, inhibitor and catalyst; wherein the UV monomer includes a first monomer and a second monomer;

[0068] S20, mixing anhydride and the first monomer to react to obtain a mixed half ester acid;

[0069] S30, mixing epoxy resin, acrylic acid, a second monomer, a polymerization inhibitor and a catalyst with a mixed half-ester acid, and performing an esterification reaction to obtain a hydrophobic bio-based UV-curable resin.

[0070] The embodiment of the present application provides a method for preparing a hydrophobic bio-based UV-curable resin, wherein tung oil anhydride in the acid anhydride is used to undergo a ring-opening reaction with the hydroxyl group in the hydroxyethyl acrylate molecule in the UV monomer, thereby introducing the main molecular structure of tung oil into the resin molecular structure, and then after the resin is formed into a film, it has performance characteristics such as hydrophobicity and flexibility similar to tung oil. However, since the tung oil anhydride itself has a large molecular weight, when used in combination with other organic anhydrides, it can effectively reduce the viscosity of the resin product, which is beneficial to the coating construction using this resin, and the overall preparation process is simple and low-cost.

[0071] In the application, the synthesis of mixed half-ester acid in step S20 is mainly to give priority to the reaction between anhydride and hydroxyl, which is conducive to the synthesis reaction in the direction we expect, so as to avoid the occurrence of side reactions when the two steps are carried out simultaneously, because in this design, after the ring-opening reaction of S30 epoxy group and carboxyl group, a hydroxyl group will be generated, and this hydroxyl group also has the possibility of reacting with anhydride. In this way, the reaction is controlled to proceed in the expected direction, the generation of by-products is reduced, and the yield is improved.

[0072] In step S10, in some embodiments, the first monomer is any one of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxyethyl methacrylate. Preferably, the first monomer is hydroxyethyl acrylate. The second monomer is 1,6-hexanediol diacrylate.

[0073] In step S20, an acid anhydride is mixed with a first monomer to react to obtain a mixed half-ester acid, including:

[0074] S21, heating the reaction system; in a preferred embodiment, a reaction kettle is used as the reaction container.

[0075] S22, when the temperature of the reaction system rises to 90°C to 110°C, keep it warm for 1.5h to 2.5h; in a preferred embodiment, the temperature of the reaction system rises to about 90°C and keeps it warm for 2h. This can ensure that the esterification reaction between the anhydride and the monomer proceeds smoothly without causing side reactions or decomposition. Controlling the insulation time can ensure that the reactants are fully converted and improve the purity and yield of the final product.

[0076] S23. Detect the acid value. When the acid value is within the range of 110KOH / g to 130mgKOH / g, cool down to 50℃ to 70℃ to obtain a mixed half-ester acid. The acid value is an important indicator to measure the degree of reaction. When the acid value reaches 110mgKOH / g to 130mgKOH / g, it means that the reaction between the anhydride and the monomer has reached the expected degree and the required half-ester acid has been formed. Timely cooling can prevent overreaction, avoid the generation of unnecessary by-products or excessive cross-linking, and affect the performance of the final product. By accurately controlling the acid value, it can be ensured that the quality and performance of the final product meet the requirements, such as appropriate acidity, molecular weight and reactivity.

[0077] In this way, by heating and heat preservation, the reactants are ensured to react fully, and the reaction rate and conversion rate are improved. The reaction is carried out within a suitable temperature range to avoid side reactions and decomposition, and the required half-ester acid is ensured to be generated. The reaction endpoint is monitored by detecting the acid value to ensure that the acid value of the final product is within the predetermined range, thereby improving the quality and performance of the product. Reasonable temperature and time control can simplify the process flow and improve production efficiency and economy.

[0078] In step S30, the esterification reaction conditions include:

[0079] S31, controlling the reaction temperature at 85°C to 95°C for 0.5h to 1.5h;

[0080] S32, controlling the reaction temperature at 100°C to 105°C for 0.5h to 1.5h;

[0081] S33, controlling the reaction temperature at 115°C to 117°C for 1.5h to 2.5h;

[0082] S34, detecting the acid value once every hour until the acid value drops to 3 mgKOH / g to 8 mgKOH / g, then cooling and evacuating at 60° C. to 90° C. to obtain the hydrophobic bio-based UV-curable resin.

[0083] In this way, by controlling the reaction temperature and time in stages, the esterification reaction can be carried out efficiently and controllably, and the reaction rate and conversion rate can be improved. By regularly testing the acid value and monitoring the reaction progress in real time, the reaction can be ensured to be complete and overreaction can be avoided. By precisely controlling the reaction conditions and vacuum treatment, the quality and performance of the final product can be ensured to meet the requirements, such as appropriate acidity, molecular weight and reactivity. Reasonable temperature and time control, combined with acid value testing and vacuum treatment, can simplify the process flow and improve production efficiency and economy.

[0084] In step S31, stage 1: control the reaction temperature at 85°C to 95°C for 0.5h to 1.5h. The low temperature insulation in the initial stage helps to start and preliminarily carry out the esterification reaction. Gentle start, 85°C to 95°C is a relatively mild temperature range, which can avoid excessive reaction and reduce the occurrence of side reactions. At this temperature, the anhydride and the epoxy resin begin to undergo a preliminary esterification reaction to generate a partial esterification product. The lower temperature helps the reactants to be better mixed and evenly distributed, laying the foundation for the subsequent high temperature reaction.

[0085] In step S32, stage two: control the reaction temperature at 100°C to 105°C for 0.5h to 1.5h. The medium temperature insulation stage further promotes the esterification reaction and increases the reaction rate. Increase the reaction rate: The temperature range of 100°C to 105°C can significantly increase the reaction rate and accelerate the esterification reaction. Form more esterification products: At this temperature, more anhydride reacts with the epoxy resin to generate more esterification products. Reduce unreacted products: Medium temperature insulation helps to reduce unreacted anhydride and epoxy resin and increase the conversion rate of the reaction.

[0086] In step S33, stage three: control the reaction temperature at 115°C to 117°C for 1.5h to 2.5h. The high temperature insulation stage ensures that the esterification reaction is completely carried out to generate the final esterification product. Complete the esterification reaction: 115°C to 117°C is a relatively high temperature range, which can ensure that the esterification reaction is completely carried out to generate the final esterification product. Improve the conversion rate: High temperature insulation helps to further improve the conversion rate of the reaction and reduce unreacted products. Reduce side reactions: Although the temperature is high, by precisely controlling time and temperature, the occurrence of side reactions can be reduced and the main reaction can be ensured.

[0087] In step S34, an acid value test is performed to monitor the progress of the reaction and ensure that the reaction is completely carried out. Monitor the reaction endpoint: The acid value is tested once an hour to monitor the progress of the reaction in real time and ensure that the esterification reaction reaches the predetermined level. Avoid overreaction: When the acid value drops to 3mgKOH / g~8mgKOH / g, it indicates that the esterification reaction has been basically completed, and the reaction can be stopped in time to avoid excessive reaction to generate unnecessary by-products. Improve product quality: By accurately controlling the acid value, it can be ensured that the quality and performance of the final product meet the requirements, such as appropriate acidity, molecular weight and reactivity.

[0088] Vacuum treatment: Vacuum at 60℃~90℃ to remove volatile substances and residual solvents in the reaction system. Removal of volatiles: Vacuum can effectively remove volatile substances in the reaction system, such as moisture, low-boiling point solvents, etc., to improve the purity of the product. Improve stability: Removal of volatiles can improve the chemical stability and physical properties of the final product. Vacuum treatment helps to optimize the mechanical properties, chemical resistance and heat resistance of the product.

[0089] Example

[0090] Example 1

[0091] This embodiment provides a coating, including a hydrophobic bio-based UV-curable resin, wherein the preparation method of the hydrophobic bio-based UV-curable resin includes the following steps:

[0092] S10, providing preparation raw materials:

[0093] Component A: 220 parts of tung oil anhydride, 75 parts of phthalic anhydride, 20 parts of tetrahydrophthalic anhydride, 20 parts of hexahydrophthalic anhydride, and 150 parts of hydroxyethyl acrylate;

[0094] Component B: composed of 380 parts of 128 epoxy resin, 75 parts of acrylic acid, 200 parts of 1,6-hexanediol diacrylate, 3 parts of p-hydroxyanisole, and 10 parts of triphenylphosphine.

[0095] S20, putting component A into a reactor, locking the reactor and heating it up, when the temperature reaches 90°C, keeping it at 90°C to 110°C for 120 minutes, and when the acid value is within the range of 110 to 130 mgKOH / g, cooling it down to below 60°C to obtain a mixed half-ester acid.

[0096] S30, adding component B material into the mixed half-ester acid obtained in step S20, continuing to heat up to 85°C, and keeping it at 85-95°C for 1 hour, continuing to heat up to 100°C, and keeping it at 100-105°C for 1 hour, continuing to heat up to 115°C, and keeping it at 115-117°C for 2 hours, starting to measure the acid value, and then measuring it once every hour. When the acid value drops to about 5 mgKOH / g, cool it down to below 90°C, evacuate at 60-90°C for 30 minutes, cool it down, discharge it and package it.

[0097] Example 2

[0098] This embodiment provides a coating, including a hydrophobic bio-based UV-curable resin, wherein the preparation method of the hydrophobic bio-based UV-curable resin includes the following steps:

[0099] S10, providing preparation raw materials:

[0100] Component A: 430 parts of tung oil anhydride, 40 parts of phthalic anhydride, 20 parts of tetrahydrophthalic anhydride, 20 parts of hexahydrophthalic anhydride, and 150 parts of hydroxyethyl acrylate;

[0101] Component B: composed of 450 parts of 128 epoxy resin, 110 parts of acrylic acid, 240 parts of 1,6-hexanediol diacrylate, 3 parts of p-hydroxyanisole, and 8 parts of triphenylphosphine.

[0102] S20, putting component A into a reactor, locking the reactor and heating it up, when the temperature reaches 90°C, keeping it at 90°C to 110°C for 120 minutes, and when the acid value is within the range of 110 to 130 mgKOH / g, cooling it down to below 60°C to obtain a mixed half-ester acid.

[0103] S30, adding component B material into the mixed half-ester acid obtained in step S20, continuing to heat up to 85°C, and keeping it at 85-95°C for 1 hour, continuing to heat up to 100°C, and keeping it at 100-105°C for 1 hour, continuing to heat up to 115°C, and keeping it at 115-117°C for 2 hours, starting to measure the acid value, and then measuring it once every hour. When the acid value drops to about 5 mgKOH / g, cool it down to below 90°C, evacuate at 60-90°C for 30 minutes, cool it down, discharge it and package it.

[0104] Example 3

[0105] This embodiment provides a coating, including a hydrophobic bio-based UV-curable resin, wherein the preparation method of the hydrophobic bio-based UV-curable resin includes the following steps:

[0106] S10, providing preparation raw materials:

[0107] Component A: 220 parts of tung oil anhydride, 40 parts of phthalic anhydride, 20 parts of tetrahydrophthalic anhydride, 58 parts of hexahydrophthalic anhydride, and 140 parts of hydroxyethyl acrylate;

[0108] Component B: composed of 380 parts of 128 epoxy resin, 72 parts of acrylic acid, 200 parts of 1,6-hexanediol diacrylate, 4 parts of p-hydroxyanisole, and 10 parts of triphenylphosphine.

[0109] S20, putting component A into a reactor, locking the reactor and heating it up, when the temperature reaches 90°C, keeping it at 90°C to 110°C for 120 minutes, and when the acid value is within the range of 110 to 130 mgKOH / g, cooling it down to below 60°C to obtain a mixed half-ester acid.

[0110] S30, adding component B material into the mixed half-ester acid obtained in step S20, continuing to heat up to 85°C, and keeping it at 85-95°C for 1 hour, continuing to heat up to 100°C, and keeping it at 100-105°C for 1 hour, continuing to heat up to 115°C, and keeping it at 115-117°C for 2 hours, starting to measure the acid value, and then measuring it once every hour. When the acid value drops to about 5 mgKOH / g, cool it down to below 90°C, evacuate at 60-90°C for 30 minutes, cool it down, discharge it and package it.

[0111] The resin prepared in the above example was made into UV curing wood coating for performance testing, and the test results are as follows:

[0112]

[0113] The test results show that the hydrophobic bio-based UV-curable resin prepared by the preparation method of the present invention has flexibility, good adhesion and good hydrophobicity when used as a coating, while other properties (hardness, stability, etc.) are not significantly different from those of commercially available epoxy acrylates.

[0114] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0115] The above-described embodiments are only used to illustrate the technical solutions of the embodiments of the present application, rather than to limit them. Although the embodiments of the present application are described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the embodiments of the present application, and should all be included in the protection scope of the embodiments of the present application.

Claims

1. A hydrophobic bio-based UV-curable resin, characterized in that: The invention comprises the following raw materials in parts by weight: 380-450 parts of epoxy resin; Acrylic acid 70-100 parts; 260-700 parts of acid anhydride; 300-400 parts of UV monomer; 2 to 4 parts of inhibitor; 4 to 10 parts of catalyst; Wherein, the acid anhydride includes tung oil anhydride.

2. The hydrophobic bio-based UV-curable resin according to claim 1, characterized in that: The acid anhydride also includes phthalic anhydride; Wherein, the weight ratio of the tung oil anhydride to the phthalic anhydride is (20-45): (2-12).

3. The hydrophobic bio-based UV-curable resin according to claim 2, characterized in that: The acid anhydride further comprises tetrahydrophthalic anhydride and hexahydrophthalic anhydride, and the weight ratio of the phthalic anhydride, the tetrahydrophthalic anhydride and the hexahydrophthalic anhydride is (1-6):(1-6):(1-6).

4. The hydrophobic bio-based UV-curable resin according to claim 1, characterized in that: The UV monomers include any two of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and 1,6-hexanediol diacrylate.

5. The hydrophobic bio-based UV-curable resin according to claim 1, characterized in that: The epoxy resin is 128 epoxy resin; And / or, the polymerization inhibitor is any one of p-hydroxyanisole and hydroquinone; And / or, the catalyst is any one of triphenylphosphine, triethylamine, dimethylbenzylamine, triethylbenzylammonium chloride, triphenylphosphine, triphenylantimony, chromium acetylacetonate, and tetraethylammonium bromide.

6. A method for preparing a hydrophobic bio-based UV-curable resin, characterized in that: include: The hydrophobic bio-based UV-curable resin according to any one of claims 1 to 5 is prepared by providing raw materials: epoxy resin, acrylic acid, acid anhydride, UV monomer, inhibitor and catalyst; wherein the UV monomer comprises a first monomer and a second monomer; Mixing the acid anhydride with the first monomer to react to obtain a mixed half-ester acid; The epoxy resin, the acrylic acid, the second monomer, the polymerization inhibitor and the catalyst are mixed with the mixed half-ester acid to perform an esterification reaction to obtain the hydrophobic bio-based ultraviolet curing resin.

7. The preparation method according to claim 6, characterized in that: The first monomer is any one of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxyethyl methacrylate; The second monomer is 1,6-hexanediol diacrylate.

8. The preparation method according to claim 6, characterized in that: The step of mixing the acid anhydride with the first monomer to obtain a mixed half-ester acid comprises: heating the reaction system; When the temperature of the reaction system rises to 90°C to 110°C, keep it warm for 1.5h to 2.5h; The acid value is detected. When the acid value is within the range of 110 KOH / g to 130 mg KOH / g, the temperature is lowered to 50° C. to 70° C. to obtain the mixed half-ester acid.

9. The preparation method according to claim 6, characterized in that: The esterification reaction conditions include: Control the reaction temperature at 85°C to 95°C and keep it for 0.5h to 1.5h; Control the reaction temperature at 100°C to 105°C for 0.5h to 1.5h; Control the reaction temperature at 115°C to 117°C and keep it for 1.5h to 2.5h; The acid value is detected once every hour until the acid value drops to 3 mgKOH / g to 8 mgKOH / g, then the temperature is lowered and vacuum is drawn at 60° C. to 90° C. to obtain the hydrophobic bio-based UV-curable resin.

10. A coating, characterized in that: It comprises the hydrophobic bio-based UV-curable resin described in any one of claims 1 to 5 or the hydrophobic bio-based UV-curable resin prepared by the preparation method described in any one of claims 6 to 9.

Citation Information

Cited By

  • Preparation method and application of solvent-free photopolymerization hydrophobic coating

    CN121023815A